Peran Supervisi dalam meningkatkan Profesionalisme Pendidik - Putri Junita Neno Lestari; Shofiyyah Shofiyyah; Nur Fitriani Ginting; Muhammad (JITU Jurnal Ilmiah Tarbiyah Umat, 2025)
This study recommends that all schools implement educational supervision within their institutions, as its application can significantly enhance overall education quality. The research design used in this article is library research employing a qualitative approach. The findings indicate that educational supervision has a substantial influence on the professionalism of educators and contributes to improving the quality of educational institutions. This research further highlights the role of supervision in strengthening educator professionalism, with the broader aim of producing high-quality educators, shaping a capable future generation, and developing strong and effective educational institutions.